2019
DOI: 10.1016/j.jallcom.2018.09.161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silver ion concentration on dielectric characteristics of Li2O-Nb2O5-P2O5 glasses

Abstract: In this work we have studied the dielectric properties of Li 2 O-Nb 2 O 5 -P 2 O 5 : Ag 2 O glasses as a function of Ag 2 O concentration. Auxiliary studies viz., optical absorption, photoluminescence (PL)and IR spectra have also been performed on these glasses. IR spectral studies have indicated that the host glass network doped with 1.0 mol% of Ag 2 O is highly polymerized. Optical absorption and PL studies have clearly exhibited absorption and emission bands due to surface plasmon resonance (SPR). From thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…It is also observed that high amounts of Li + and their small inter-particle contacts are responsible for thermal conductivity up to an extent in this glassy system due to high lattice waves. The Effect of silver ion density may change in the dielectric properties of glassy systems containing Li 2 O [14]. It is also observed from the literature [14] that space charge polarization should act as a major part in changing the values of dielectric constant of Li 2 O-doped glassy systems.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is also observed that high amounts of Li + and their small inter-particle contacts are responsible for thermal conductivity up to an extent in this glassy system due to high lattice waves. The Effect of silver ion density may change in the dielectric properties of glassy systems containing Li 2 O [14]. It is also observed from the literature [14] that space charge polarization should act as a major part in changing the values of dielectric constant of Li 2 O-doped glassy systems.…”
Section: Introductionmentioning
confidence: 90%
“…The Effect of silver ion density may change in the dielectric properties of glassy systems containing Li 2 O [14]. It is also observed from the literature [14] that space charge polarization should act as a major part in changing the values of dielectric constant of Li 2 O-doped glassy systems. Higher Li + doped oxide layered material containing Mg and La-cohave also been found to be promising candidates for exhibiting good electrochemical performance [15].…”
Section: Introductionmentioning
confidence: 90%
“…Por exemplo, a taxa de degradação de CaO-Na 2 O-P 2 O 5 pode variar de horas até semanas, dependendo da composição do vidro. Bertran e colaboradores 29 30 Estudos espectrais mostram aglomerados de partículas de prata metálica e íons Ag + nos vidros fabricados. Os vidros dopados com maior teor de Ag 2 O mostraram os maiores valores de constante dielétrica, especialmente em baixas frequências e altas temperaturas.…”
Section: Uso Em Vidrosunclassified
“…Niobium phosphate glasses possess remarkable functional properties which make them attractive for diverse fields of application, from optical and laser technology, 1–6 electrochemical devices 7–13 to nuclear waste immobilization, 14 and biomedicine 15,16 . Generally, the addition of niobium oxide to phosphate glass increases density, glass transition temperature, elastic modulus, refractive index, improves chemical durability, and decreases thermal expansion coefficient 2–4,14,17 …”
Section: Introductionmentioning
confidence: 99%
“…In combination with alkali oxide, niobium oxide can be incorporated in a phosphate network in a wide compositional range which makes these glass systems interesting from the point of view of electrical properties. Indeed, studies on niobium phosphate glasses containing different alkali oxides, 7–10,13,21 as well as their mixture 12 reveal that structural modifications induced by the incorporation of niobium into phosphate glass have a significant impact on the ionic conductivity. Moreover the study by Graça et al 8 on alkali niobium phosphate glasses shows that while ionic transport takes place above room temperature, at lower temperatures niobium actively contributes to the electrical processes by the electron transfer between niobium ions in different valence states, that is, Nb 5+ and Nb 4+ .…”
Section: Introductionmentioning
confidence: 99%